Developing Halal Tourism in Indonesia: Strategies, Opportunities, and Challenges for Global Competitiveness - Fusthathul Nur Sasongko (Journal of Economic Perspectives and Business Innovation, 2025)
AbstractHalal tourism has emerged as a strategic sector with strong potential to enhance Indonesia’s global competitiveness in the tourism industry. This study examines the strategies, opportunities, and challenges involved in developing halal tourism as a sustainable economic driver. Using a qualitative descriptive approach, the research analyzes tourism policies, industry practices, and market trends related to Muslim-friendly travel services. The findings indicate that Indonesia possesses significant opportunities due to its cultural diversity, natural attractions, and large domestic Muslim population. Strategic development requires integrated policies, infrastructure improvement, service standardization, and international branding. However, challenges remain in the form of regulatory coordination, limited awareness among stakeholders, and uneven service quality across regions. The study concludes that strengthening collaboration between government, industry actors, and local communities is essential to position Indonesia as a leading global halal tourism destination. Keywords: halal tourism, tourism development, global competitiveness, Indonesia tourism, sustainable tourism